Research on the Influencing Factors and Promotion Strategies of Food Supply Chain Resilience - HAN Guang-he; PAN Xin; ZHANG Xin; SUN Wei-ren (Liang you shipin ke-ji)
The resilience of food supply chain is related to food security. It is of practical significance to explore the influencing factors of the resilience of food supply chain. Based on the literature research method and expert interview method, 20 important factors affecting the resilience of food supply chain were identified from four dimensions, including prediction ability, resistance ability, recovery ability and growth ability. The comprehensive DEMATEL-ISM model was constructed and the ISM hierarchical structure diagram is drawn. On the basis of exploring the importance and influence of each factor on the resilience of food supply chain, the key influencing factors were identified, and the ISM was used to divide each factor into levels and clarify the interaction between each factor. The results showed that the four factors of policy support, policy and market changes, information sharing ability, digital technology application and innovation were the key influencing factors of food supply chain resilience, and they were also the deepest fundamental factors. Predictive capability and growth capability affect the resistance and recovery capabilities of the grain supply chain resilience, and serve as the foundation of resilience capability, directly influencing the resilience of the grain supply chain. Based on the research conclusions, targeted suggestions are provided for enhancing the resilience of China’s grain supply chain.